Provisions Before Marriage to Make Indonesian Urban Muslim Families More Resilient: A al-Maslahah al-Mursalah Perspective - Jalili, Ahmad; Saleh, Ahmad Syukri; Ramlah (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2023)
The implementation of premarital provision has been regulated in Director General of Islamic Community Guidance Regulation No. DJ.II/542 of 2013. This study discusses the effectiveness of premarital provision as a family resilience effort based on the concept of al-maṣlaḥah al-mursalah, especially at the KUA of the Kepulauan Riau Province. This study uses qualitative research methods in the form of field research. The approach used is empirical and juridical. The sources of data in this study are divided into two categories, namely primary and secondary. The data collection techniques used are observation, interview, and documentation. The results of this study show that the premarital training that took place at the KUA in the Kepulauan Riau Province has not been effective as an effort for family resilience. Based on al-maṣlaḥah al-mursalah, premarital provision is included in al-maṣlaḥah al-hajiyyah because it is not part of the pillars and conditions of marriage. Premarital training is actually very effective as an effort to maintain family resilience, because with premarital training, it makes perfection for the prospective bride and groom, namely to gain knowledge about marriage for the sake of creating a family sakinah, mawaddah, and warahmah.